Insomniacs after school. 4 - Ojiro, Makoto, 1982- (VIZ Media, LLC, 2023)
"Two sleepless teenagers find kinship as they escape to their school's astronomy observatory. Unable to sleep at night, Ganta Nakami is cranky in class and unpopular with his classmates. He discovers that the school observatory, once used by the now-defunct astronomy club, may be the perfect place for a nap--but he's not alone. Fellow insomniac Isaki Magari is willing to share the observatory with Nakami, and a friendship between the two begins as they bond over the most unlikely things. After discovering the source of Magari's insomnia, Nakami and Magari implement a new nighttime routine, hoping to improve their sleep. With the Perseid meteor shower viewing party and the national photo contest still to come, it's shaping up to be an eventful summer for this pair of insomniacs!"--